Evaluasi Pengetahuan Peserta Didik SMA di Kotagede Yogyakarta melalui Edukasi Pertolongan Pertama Kegawatdaruratan - Ikhsan, Raodah Tul (Jurnal Nusantara Mengabdi, 2025)
Purpose: This program aims to improve students' knowledge of emergency response in the school environment. Method: The activity was conducted at Darussalam Islamic High School in Kotagede, in November 2025, involving 19 students. The intervention consisted of a pre-test, lecture, demonstration, hands-on practice, post-test, and satisfaction evaluation. Knowledge was measured using a multiple-choice questionnaire consisting of 10 questions, while satisfaction was evaluated using an instrument containing 25 Likert scale. Data analysis used a descriptive approach. SWOT analysis was also used to assess the implementation context and opportunities for program sustainability. Results: The average knowledge score increased from 4.58 to 6.53, or an increase of 42.6%. The satisfaction level of participants reached 84.7% (88% for resource persons' reactions; 83% for educational delivery; 84% for the activity environment), indicating positive acceptance and relevance of the material to the participants' needs. SWOT analysis indicated strengths in material suitability, facilitator competence, and applicable methods; opportunities were seen in ongoing cooperation and implementation of similar programs at partner schools. Conclusion: School-based first aid education effectively improves knowledge of emergency first aid and received positive responses, making it a suitable model for promotional interventions in educational settings. Limitations: The scope of participants was limited, as it was only conducted in one school, and it did not evaluate long-term knowledge retention and practical skills in depth. Contribution: This program has the potential to be further developed through continuous cooperation so that it can strengthen school preparedness for emergency situations more comprehensively.